Assessing viability of a minimally invasive autopsy technique in ascertaining the probable cause of death in patients who were SARS CoV19 positive at the time of their demise - Ajay H. Bhandarwar; Girish D. Bakhshi; Eham Arora; Nikhil Dhimole; Sanjay R. Bijwe; Shubhangi V. Agale; Megha S. Kinake; Shilpa Domkundwar; Yogesh Thube (BMC, 2021)
Abstract Background SARS CoV-19 was declared as a pandemic by the World Health Organization (WHO), raising up challenges on various levels ranging from therapeutics to diagnostics. The conventional autopsy technique may pose a health hazard to health care workers. A minimally invasive autopsy technique can diminish this hazard. Materials and methods Between August and November 2020, 51 patients who were suffering from Covid-19 at the time of their demise were included. A novel minimally invasive ultrasound-guided technique for procuring tissue samples of major organs was employed which were thereafter subject to histopathological examination. A detailed review of the course in hospital was noted. An analysis was performed to correlate the cause of death ascertained from our minimally invasive technique with the cause of death ascertained clinically. Results There was adequate tissue sampling in 45 cases, where the minimally invasive autopsy technique confirmed the cause of death in all 45 cases (100%) and made it more specific in 5 cases (11.11%). Conclusion Minimally Invasive Autopsy is an easily reproducible technique which has the potential to strengthen the probable the cause of death with reasonable certainty while ensuring safety and ethics.